Electrochemical Sensor Based on Spent Coffee Grounds Hydrochar and Metal Nanoparticles for Simultaneous Detection of Emerging Contaminants in Natural Water - Barreto, Francisco Contini [UNESP]; Ito, Erika Yukie [UNESP]; Mounienguet, Naelle Kita [UNESP]; Dal’ Evedove Soares, Letícia [UNESP]; Yang, Jie; He, Quan; Cesarino, Ivana [UNESP] (MDPI, 2023)
This research describes the modification of a glassy carbon electrode with spent coffee grounds hydrochar (HDC) and copper nanoparticles (CuNPs) for the simultaneous determination of hydroxychloroquine sulfate (HCS) and bisphenol A (BPA). Scanning electron microscopy, EDS and cyclic voltammetry were used to characterize the nanocomposite. The analytical parameters were optimized and the sensing platform was applied for the determination of HCS and BPA using square-wave voltammetry (SWV). For HCS, the linear range was from 1.0 μmol L−1 to 50 μmol L−1, with an LOD and LOQ of 0.46 and 1.53 μmol L−1, respectively. For BPA, the linear range was from 0.5 μmol L−1 to 10 μmol L−1, with an LOD and LOQ of 0.31 μmol L−1 and 1.06 μmol L−1, respectively. Finally, the developed electrochemical sensor was applied for the quantification of the emerging contaminants in natural water, with recoveries between 94.8% and 106.8% for HCS and 99.6% and 105.2% for BPA. Therefore, HDC-CuNPs demonstrated themselves to be a good alternative as a sustainable and cheaper material for application in electroanalyses.
Keywords: bisphenol A; chloroquine; copper nanoparticles; electrochemical sensor; emerging contaminants; hydrochar